Green Hydrogen Management in ASEAN Countries from Investment Law Perspective - Rahayu, Sang Ayu Putu; Puteri, Dina Silvia; Anitasari, Rahayu Fery; Nur, Asrul Ibrahim Nur (Indonesian Journal of Environmental Law and Sustainable Development, 2025)
The development of green energy is a global priority in facing the challenges of climate change, where green hydrogen has emerged as a renewable energy that can be a sustainable solution. This article discusses the comparison of green hydrogen management in ASEAN countries from an investment law perspective. The main focus of this study is to analyze the regulations, incentives, and legal barriers faced by investors in the green hydrogen sector in various ASEAN member countries. The research method used involves a qualitative approach with a literature study and analysis of laws and regulations related to renewable energy investment. The results of the study show that there are policy disparities among ASEAN countries in supporting green hydrogen investment. Singapore and Malaysia, for example, have adopted more progressive policies, including fiscal incentives and ease of licensing, while other countries still face complex regulatory challenges and lack of supporting infrastructure. This article concludes that harmonization of the investment legal framework in ASEAN is needed to attract more investment in the green hydrogen sector. In addition, strong regional collaboration can accelerate the development of green hydrogen technology and strengthen energy security in the region.